A RELIGION OF RECONCILIATION: INDOCTRINATION OF ISLAM RAHMATAN LIL 'ALAMIN IN JAMBI ISLAMIC BOARDING SCHOOL - Nofarita Asyiah; Yahya Shaykh Ahmad (Yayasan Dinamika Literasi Jambi, 2026)
This study examines the role of Islamic boarding schools in Jambi as a strategic space in sowing the values ​​of Islam rahmatan lil 'alamin through a systematic and contextual indoctrination process. The main focus is directed at how the concept of Islam that brings blessings to the universe is internalized to students through a typical Islamic boarding school educational approach. This study reveals that the indoctrination is not coercive, but rather packaged in a framework of Islamic values ​​that emphasize peace, tolerance, and openness. Islamic boarding schools in Jambi play a dual role as scientific institutions as well as centers of social transformation that foster moderate Islamic character in a pluralistic society. Through a structured and adaptive curriculum, the values ​​of Islam rahmatan lil 'alamin are integrated into various subjects and religious activities, making the curriculum the center of the entire indoctrination process. By tracing the dynamics of education in Islamic boarding schools, this study confirms that the indoctrination of Islam rahmatan lil 'alamin is not only a process of inheriting values, but also a form of forming spiritual awareness, sowing messages of peace and comprehensive social.